MiR-192 and miR-662 enhance chemoresistance and invasiveness of squamous cell lung carcinoma. (April 2018) - Filipska, Martyna; Skrzypski, Marcin; Czetyrbok, Katarzyna; Stokowy, Tomasz; Stasiłojć, Grzegorz; Supernat, Anna; Jassem, Jacek; Żaczek, Anna J.; Bigda, Jacek
Highlights: Aggressive biology of squamous cell lung cancer (SCC) is mediated by miRNA. MiR-192 and miR-662 enhance invasiveness and anchorage independent growth. Resistance to etoposide but not to cisplatin is imparted by miR-192 and miR-662. MiR-192 and miR-662 enhance expression of EMT- and WNT-activating genes. MiR-192 and miR-662 down-regulate the expression of immunogenic genes. Abstract: Objectives: Overexpression of miR-192, miR-192* and miR-662 was previously found to correlate with poor prognosis of early-stage squamous cell lung cancer (SCC) patients. In this study, we investigated the relevance of these miRNAs to cancer cell biology and chemoresistance. Materials and methods: MiRNA expression profile was analysed in 10 non-small cell lung cancer (NSCLC) cell lines using RT-qPCR. H520 and H1703 cells were transfected with miRNA inhibitors (anti-miR-192, -192* and -662) for functional studies. Chemoresistance to cisplatin and etoposide was evaluated using MTT colorimetric assay. H520 cells were subjected to 3D soft-agar colony formation assay and H1703 cells to wound healing assay. Whole transcriptome analysis was used to assess the effect of miR-192 and miR-662 inhibition on gene expression. Results: SCC cell lines, H520 and H1703, differed in miRNA expression and phenotypic features. MiR-192 and miR-662 inhibition decreased clonogenicity and motility of SCC cells. MiR-192 and miR-662 inhibition sensitized SCC cells to etoposide but not to cisplatin. Whole transcriptome analysis revealed genes regulated by miR-192 and miR-662 in SCC, relevant to maintaining chemoresistance, invasiveness, epithelial-mesenchymal transition (EMT) and immune evasion. Conclusions: We showed for the first time that miR-192 and miR-662 have functional role in SCC cells. Our findings suggest that targeting these miRNAs may impact both chemoresistance and invasiveness of SCC, and add to the evidence linking these aspects of tumour biology. Overexpression of miR-192 and miR-662 might be useful as a marker of resistance to etoposide.